2020
DOI: 10.1049/iet-com.2019.1316
|View full text |Cite
|
Sign up to set email alerts
|

Likelihood ascent search augmented sphere decoding receiver for MIMO systems using M‐QAM constellations

Abstract: MIMO systems employing sphere decoding (SD) algorithm are known to achieve near maximum likelihood (ML) performance at a reduced complexity by restricting the candidate search space to a sphere of a certain radius. The performance of SD depends on the precise estimation of its soft output. In this paper, a low complexity modified Likelihood Ascent Search (LAS) algorithm is proposed to be used within a SD receiver in order to precisely estimate the counter-hypothesis for its winner candidates. The LAS algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The MIMO detection problem based on the optimal ML detection algorithm is equivalent to minimize the Euclidean distance and solving the problem based on criterion [9] x = min…”
Section: System Modelmentioning
confidence: 99%
“…The MIMO detection problem based on the optimal ML detection algorithm is equivalent to minimize the Euclidean distance and solving the problem based on criterion [9] x = min…”
Section: System Modelmentioning
confidence: 99%
“…Recently, several optimal and sub-optimal MIMO detection algorithms have been proposed in the literature and can be broadly characterized into maximum likelihood (ML) detection [4]- [9], linear detectors [10], [11], interference cancellation based algorithms [12], [13], graph-based [14], [15], sparsity boosted [16]- [18], lattice-reduction-based [19]- [21] and neighborhoodsearch-based algorithms [22]- [28]. The optimal detector, such as ML and maximum a posteriori (MAP), recover all the symbols jointly and simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…The soft-output SD algorithm for MIMO and distributed antenna systems was proposed in [8], [9], where the authors showed that for the worst-case scenario the SD's performance could be improved by precise and low-complexity estimation of soft-output for SD. Nevertheless, the detection complexity of SD is still higher in high dimensional MIMO systems.…”
Section: Introductionmentioning
confidence: 99%